A Framework for Policies and Practices to Improve Test Security Programs: Prevention, Detection, Investigation, and Resolution (PDIR). Issue 3 (22nd May 2017) - Ferrara, Steve
Abstract : Test security is not an end in itself; it is important because we want to be able to make valid interpretations from test scores. In this article, I propose a framework for comprehensive test security systems: prevention, detection, investigation, and resolution. The article discusses threats to test security, roles and responsibilities, rigorous training for everyone involved in testing, and an evaluation of current practices in test security. I call on everyone responsible for testing programs—the Association of Test Publishers, Council of Chief State School Officers, National Council on Measurement in Education, U.S. Department of Education, and state assessment program managers, their vendors, and the research community—to collaborate on guidelines and practices for security violation prevention, detection, investigation, and resolution.